DEVELOPMENT OF AUGMENTED REALITY (AR) LEARNING MEDIA ON THE SUBJECT OF BASIC ELECTRONICS: BASIC CONCEPTS OF ELECTRICAL CURRENT FOR VOCATIONAL SCHOOL STUDENTS IN THE FIELD OF ELECTRONICS EXPERTISE - Shalsa Bila Amania; Hendra Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
One of the causes of the lack of conceptual understanding of Vocational High School (SMK) students in the field of electronics expertise is the discrepancy between the passive way of delivering learning and the nature of student learning as a generation that prioritizes visual and digital. This has an impact on the low mastery of basic competencies of graduates, especially in understanding abstract and invisible material. One of the most affected materials is the basic concept of electric current, which is the main foundation for understanding advanced electronics materials. This study aims to create a learning media based on Augmented Reality (AR) with Assemblr EDU platform to visualize the basic concepts of electric current, as well as test its feasibility as a learning aid. The research method used is Multimedia Development Life Cycle (MDLC) which includes concept, design, material collection, creation, and testing. The data collection technique is done through validation from material experts, media experts, and student response questionnaires. The results showed that the AR learning media that was developed was quite feasible and able to help students understand the basic concepts of electric current in a more real, visual, and interactive way, in accordance with the characteristics of vocational learning.